Factors influencing job performance among employees in Bulk and Break Bulk Terminal Department Of Johor Port Berhad / Siti Afifah Zulkefle - Zulkefle, Siti Afifah (Faculty of Business and Management, 2017)
This study is conducted to examine the factors that influence job performance among employees in Bulk and Break Bulk Terminal Department of Johor Port Berhad. The objectives of the study were: (a) to study the relationship between stress and job performance among employees (b) to study relationship between salary and job performance among employees (c) to study the relationship between work environment and job performance among employees, (d) to study the relationship between workload and job performance among employees, (e) to study the factor that lead to job performance among employees in Bulk and Break Bulk Terminal Department of Johor Port Berhad, 108 employees were selected through convenience sampling technique. To achieve the objectives, data were collected through a questionnaire probing various aspects of job performance. The data analysis showed that salary, work environment and workload has significant relationship on job performance while stress has not significant relationship with job performance among employees in Bulk and Break Bulk Terminal Department of Johor Port Berhad. The most influence factor is workload. It is recommend that management start practicing flexible work schedules. It is able to give benefit towards employees and organization. It will give less turnover, greater productivity, cost saving and co-worker development. Thus, it will get better in performing their job.